Al-Jabbar Mosque and the Sociology of Megaprojects: Giant Religious Infrastructure, Power, and Social Transformation in Indonesia - Endah Ratna Sonya; Paelani Setia (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
The Al-Jabbar Grand Mosque in Bandung, West Java, stands as one of Indonesia’s largest religious infrastructure projects and has quickly become a prominent symbol of Islamic modernity, regional identity, and religious tourism. Although its significance continues to grow, existing studies on Al-Jabbar primarily address architecture, symbolism, and tourism, with limited attention to its broader social, political, and economic impacts as a religious megaproject. This research examines the ways in which the Al-Jabbar Mosque reshapes power relations, spatial structures, and socio-economic dynamics in the Gedebage area, utilizing Bent Flyvbjerg’s megaprojects framework, including the Iron Law of Megaprojects, strategic misrepresentation, and the four sublimes. Employing a qualitative case study approach based on field observations, in-depth interviews, and literature analysis, the study finds that the Al-Jabbar Mosque serves not only as a place of worship but also as a political-urban instrument reflecting state interests, modernization agendas, and narratives of technological progress. The results indicate that the project has converted former wetlands and agricultural land into a religious-tourism hub, restructured mobility patterns, stimulated new economic activities, strengthened micro and small enterprises, and accelerated the commodification of public space. However, the distribution of benefits remains uneven. Government institutions, developers, and tourism-related actors obtain significant economic and symbolic advantages, while local residents experience increasing pressures, such as traffic congestion, waste accumulation, land-use conversion, business competition, and emerging forms of religious gentrification. These findings suggest that religious megaprojects can generate both economic opportunities and new forms of urban inequality. The study contributes to the sociology of megaprojects by introducing the concept of mega religious infrastructure as an analytical framework for understanding how large-scale religious developments intersect with power relations, urban capitalism, and socio-spatial transformation in contemporary Muslim societies.